Oral corrective feedback: Exploring the relationship between teacher's strategy and students' willingness to communicate - Lailatus Sa'adah; Joko Nurkamto; Suparno Suparno (Universitas Syiah Kuala, 2018)
This study seeks to investigate the types of oral corrective feedback implemented in class and its effect on students' willingness to communicate. As many as 35 senior high school students as well as the teacher were involved in the observation stage of this study and shared their perspectives about the relationship between teacher's feedbacks on the students' willingness to communicate through interview. The findings show that there are three types of oral corrective feedback given in the class, i.e. explicit correction, metalinguistic, and clarification request feedback. The students insist that the teacher's oral corrective feedback does not make them reluctant to communicate to their peers or teacher in the class. Therefore, it can be concluded that teacher's oral corrective feedback strategy does not disturb the interaction between the teacher and students in the class. It can be inferred that oral corrective feedback is necessary to be implemented in the class because it assists their second language learning.